Logistics management : contributions of the Section Logistics of the German Academic Association for Business Research, 2015, Braunschweig, Germany /: contributions of the Section Logistics of the German Academic Association for Business Research, 2015, Braunschweig, Germany. (2016) - Unknown
No abstract available